Renoprotective Effect of Agalsidase Alfa: A Long-Term Follow-Up of Patients with Fabry Disease - Cybulla, Markus; Nicholls, Kathleen; Feriozzi, Sandro; Linhart, Aleš; Torras, Joan; Vujkovac, Bojan; Botha, Jaco; Anagnostopoulou, Christina; West, Michael L; FOS Study Group (Journal of clinical medicine, 2022)
Fabry disease is a rare lysosomal storage disorder caused by mutations in the GLA gene, which, without treatment, can cause significant renal dysfunction. We evaluated the effects of enzyme replacement therapy with agalsidase alfa on renal decline in patients with Fabry disease using data from the Fabry Outcome Survey (FOS) registry. Male patients with Fabry disease aged >16 years at agalsidase alfa start were stratified by low (≤0.5 g/24 h) or high (>0.5 g/24 h) baseline proteinuria and by ‘classic’ or ‘non-classic’ phenotype. Overall, 193 male patients with low (n = 135) or high (n = 58) baseline proteinuria were evaluated. Compared with patients with low baseline proteinuria, those with high baseline proteinuria had a lower mean ± standard deviation baseline eGFR (89.1 ± 26.2 vs. 106.6 ± 21.8 mL/min/1.73 m2) and faster mean ± standard error eGFR decline (−3.62 ± 0.42 vs. −1.61 ± 0.28 mL/min/1.73 m2 per year; p < 0.0001). Patients with classic Fabry disease had similar rates of eGFR decline irrespective of baseline proteinuria; only one patient with non-classic Fabry disease had high baseline proteinuria, preventing meaningful comparisons between groups. In this analysis, baseline proteinuria significantly impacted the rate of eGFR decline in the overall population, suggesting that early treatment with good proteinuria control may be associated with renoprotective effects.
Keywords: enzyme replacement therapy; estimated glomerular filtration rate; proteinuria; Fabry disease